Selected Topics in Photonics (IITK Directions, 2018)
This volume comprises chapters on the cutting-edge research in photonics undertaken at IIT Kanpur. Photonics requires scientists and engineers to work closely together in addressing challenges which are interdisciplinary in nature. At IIT Kanpur, research is being pursued in several key areas of photonics namely fiber-optics, nanophotonics, quantum optics, optical spectroscopy and imaging, biophotonics, and photonic devices. This volume brings together contributions from experts to obtain a contemporary perspective in photonics research. The reader will find articles about coherent optical communications, novel photonic nanostructures, nano-structured materials for light control, optical tweezers with nanoscale applications, quantum coherence and entanglement, photodiode arrays and quantum metrology. The volume also includes chapters on cancer diagnostics with optical tomography, protein fluctuations at microsecond scale at single-molecule level, and visualization of motion in a droplet which are interdisciplinary in nature. The contents of this book will be of use to researchers, students, and professionals working across all domains of photonics. .